Identifying and Addressing Barriers to Implementing Core Electronic Health Record Use Metrics for Ambulatory Care: Virtual Consensus Conference Proceedings - Levy, Deborah R.; Moy, Amanda J.; Apathy, Nate; Adler-Milstein, Julia; Rotenstein, Lisa; Nath, Bidisha; Rosenbloom, S. Trent; Kannampallil, Thomas; Mishuris, Rebecca G.; Alexanian, Aram; Sieja, Amber; Hribar, Michelle R.; Patel, Jigar S.; Sinsky, Christine A.; Melnick, Edward R. (Applied Clinical Informatics, 2023)
Precise, reliable, valid metrics that are cost-effective and require reasonable implementation time and effort are needed to drive electronic health record (EHR) improvements and decrease EHR burden. Differences exist between research and vendor definitions of metrics.Process We convened three stakeholder groups (health system informatics leaders, EHR vendor representatives, and researchers) in a virtual workshop series to achieve consensus on barriers, solutions, and next steps to implementing the core EHR use metrics in ambulatory care.Conclusion Actionable solutions identified to address core categories of EHR metric implementation challenges include: (1) maintaining broad stakeholder engagement, (2) reaching agreement on standardized measure definitions across vendors, (3) integrating clinician perspectives, and (4) addressing cognitive and EHR burden. Building upon the momentum of this workshop's outputs offers promise for overcoming barriers to implementing EHR use metrics.
Keywords: audit logs; metrics; electronic health records and systems; data validation and verification; ambulatory care/primary care; facilitators and barriers; use, administration, and maintenance